1999
DOI: 10.1016/s0264-8172(98)00035-x
|View full text |Cite
|
Sign up to set email alerts
|

The lack of relationship between overpressure and porosity in North Sea and Haltenbanken shales

Abstract: All rights reserved. No part of this publication may be reproduced or transmitted, in any form or by any means, without permission.Cover: Inger Sandved Anfinsen. Printed in Norway: AiT e-dit AS, Oslo, 2008. Produced in co-operation with Unipub AS. The thesis is produced by Unipub AS merely in connection with the thesis defence. Kindly direct all inquiries regarding the thesis to the copyright holder or the unit which grants the doctorate. Unipub AS is owned by The University Foundation for Student Life (SiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 27 publications
6
22
0
Order By: Relevance
“…Wangen (2000) showed that overpressure also results from cementation of pore space. This is consistent with Teige et al (1999) and Nordga˚rd Bola˚s et al (2004) who showed that porosity does not always show a positive correlation to overpressure in mudstones. It therefore becomes apparent that the void ratio change used as an index of compaction is problematic because precipitation of minerals may reduce porosity without compaction while compaction may proceed but porosity increases due to dissolution.…”
Section: Introductionsupporting
confidence: 92%
“…Wangen (2000) showed that overpressure also results from cementation of pore space. This is consistent with Teige et al (1999) and Nordga˚rd Bola˚s et al (2004) who showed that porosity does not always show a positive correlation to overpressure in mudstones. It therefore becomes apparent that the void ratio change used as an index of compaction is problematic because precipitation of minerals may reduce porosity without compaction while compaction may proceed but porosity increases due to dissolution.…”
Section: Introductionsupporting
confidence: 92%
“…Previous studies have observed the lack of a relationship between porosity and effective stress in mudstones buried into the diagenetic regime (e.g., Hermanrud et al 1998;Teige et al 1999). Others have reported density increases in mudstones that are not related to effective stress but are coincident with smectite-to-illite transformation (e.g., Peltonen et al 2009;Lahann and Swarbrick, 2011), which confirms that chemical compaction may take place in association with clay diagenesis.…”
Section: Discussionmentioning
confidence: 87%
“…12B). The lack of correlation between overpressure and porosity has been demonstrated for a wide range of North Sea and Haltenbanken shales (Hermanrud et al, 1998;Teige, Hermandrud, Wensaas, & Nordgård Bolås, 1999). Teige et al therefore suggest that high formation pressure is likely to have been generated after the rocks had been normally compacted and/or that thermally controlled mineral reactions dominate the porosity reduction at temperatures and depths where diagenesis is quantitatively important.…”
Section: Basin Modellingmentioning
confidence: 99%